Associations Between Perceived Material Deprivation, Parents’ Discipline Practices, and Children's Behavior Problems: An International Perspective - Anika Schenck-Fontaine (2018)
© 2018 Society for Research in Child Development This study investigated the association between perceived material deprivation, children's behavior problems, and parents’ disciplinary practices. The sample included 1,418 8- to 12-year-old children and their parents in China, Colombia, Italy, Jordan, Kenya, the Philippines, Sweden, Thailand, and the United States. Multilevel mixed- and fixed-effects regression models found that, even when income remained stable, perceived material deprivation was associated with children's externalizing behavior problems and parents’ psychological aggression. Parents’ disciplinary practices mediated a small share of the association between perceived material deprivation and children's behavior problems. There were no differences in these associations between mothers and fathers or between high- and low- and middle-income countries. These results suggest that material deprivation likely influences children's outcomes at any income level.